1978
DOI: 10.1021/bi00603a026
|View full text |Cite
|
Sign up to set email alerts
|

Coordination complexes and catalytic properties of proteins and related substances. 93. Complete amino acid sequence of the major component myoglobin of finback whale (Balaenoptera physalus)

Abstract: The complete amino acid sequence of the major component myoglobin from finback whale, Balaenoptera physalus, was determined by the automated Edman degradation of several large peptides obtained by specific cleavages of the protein. Three easily separable peptides were obtained by cleaving with cyanogen bromide at the two methionine residues and one large peptide was isolated after cleavage with (2-p-nitrophenylsulfenyl)-3-methyl-3'-bromoindolenine. More than 60% of the covalent structure was established by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The remainder of the primary structure was determined by sequence analysis of tryptic peptides isolated from the central cyanogen T his paper reports the use of the automatic Edman degradation procedure in determining the complete amino acid sequence of the myoglobin from the Dali porpoise, Phocoenoides dalli dalli. The peptide fragmentation and the analytical procedures necessary for this determination have been established in several other cetacean myoglobin sequence papers (Dwulet et al, 1975(Dwulet et al, , 1977Bogardt et al, 1976;Jones et al, 1976Jones et al, , 1978; Wang et al, 1977;DiMarchi et al, 1978). The sequence reported here differs in only two residue positions from that reported for the common porpoise, Phocoena phocoena (Bradshaw & Gurd, 1969).…”
mentioning
confidence: 87%
“…The remainder of the primary structure was determined by sequence analysis of tryptic peptides isolated from the central cyanogen T his paper reports the use of the automatic Edman degradation procedure in determining the complete amino acid sequence of the myoglobin from the Dali porpoise, Phocoenoides dalli dalli. The peptide fragmentation and the analytical procedures necessary for this determination have been established in several other cetacean myoglobin sequence papers (Dwulet et al, 1975(Dwulet et al, , 1977Bogardt et al, 1976;Jones et al, 1976Jones et al, , 1978; Wang et al, 1977;DiMarchi et al, 1978). The sequence reported here differs in only two residue positions from that reported for the common porpoise, Phocoena phocoena (Bradshaw & Gurd, 1969).…”
mentioning
confidence: 87%
“…The further digestion of I he complete sequence reported here for the myoglobin from the humpback whale, Megaptera novaeangliae, is in total agreement with that found for the first 60 residues by Edman & Begg (1967) in their classical introduction of automated sequencing methodology. The complete amino acid sequence of the myoglobin from Amazon River dolphin (Dwulet et al, 1975), California gray whale (Bogardt et al, 1976), Atlantic bottlenosed dolphin (Jones et al, 1976), arctic minke whale , dwarf sperm whale (Dwulet et al, 1977), Pacific common dolphin (Wang et al, 1977), finback whale (DiMarchi et al, 1978a), pilot whale (Jones et al, 1978), and Dali porpoise (Meuth et al, 1978) have been reported. All l From the Department of Chemistry, Indiana University, Bloomington, Indiana 47401.…”
mentioning
confidence: 99%